Separation of nitroaromatics from wastewater by using supported ionic liquid membranes - Bhosale, Vikas K.; Chana, Harpreet K.; Kamble, Sanjay P.; Kulkarni, Prashant S. (Journal of Water Process Engineering, 2019)
Nitroaromatics have been released into wastewater during its production and application, thus, contaminating the ecosystem. The stringent discharge limits of industrial effluents have led to the development of sustainable technologies for removal of nitroaromatics from wastewater. In the present investigation, separation of nitroaromatic compounds such as TNT, TNP and Tetryl from model wastewater was investigated by using supported ionic liquid membrane (SILM) process. Various aliquat 336 based ionic liquids (ILs) were synthesised and characterized, and immobilized in PTFE and PVDF supports for the preparation of SILMs. The key parameters such as type of IL and striping phase, feed phase pH, selectivity for SILM, extraction kinetics and reuse of SILM were studied, in detail. The size of IL-anion plays an important role in removal process. The SILM was found to be selective for TNP over other nitroaromatics. Maximum separation of TNP (< 95%) was achieved with IL, [A336][SCN] within 12 h. Selectivity and reuse of the membrane indicate the potential of SILM technology as a sustainable chemical process for the treatment of nitroaromatics contaminated wastewater.
Keywords: Ionic liquid; Membrane; Nitroaromatics; Separation; wastewater

Screening of zero valent mono/bimetallic catalysts and recommendation of Raney Ni (without reducing agent) for dechlorination of 4-chlorophenol - Raut, Sandesh S.; Shetty, Rohit; Raju, Nikhi Maria; Kamble, Sanjay P.; Kulkarni, Prashant S. (Chemosphere, 2020)
Chlorophenol (CP) is considered as environmentally hazardous material due to its acute toxicity, persistent nature and strong bioaccumulation. The dechlorination of 4-CP was investigated by using various catalysts such as bimetallic (Fe-0/Cu-0, Al-0/Fe-0), Pd/C, Raney Ni and Fe-0 at room temperature. Among the catalysts studied, Raney Ni proved to be very economical and efficient catalyst that worked without the use of an external reducing agent. The dechlorination of 4-CP by Raney Ni was therefore further explored. Complete dechlorination of 4-CP (30 mg L-1) was achieved in 6 hat an optimum Raney Ni catalyst loading of 3 g L-1. The effect of triethylamine (TEA) and tripropylamine (TPA) was also investigated and it was observed that 100% dechlorination is possible in presence of 45 mg L-1 of TEA. The kinetics of dechlorination of 4-CP was investigated and found to be first order with a rate constant of 0.017 min(-1) at 50 degrees C, and it enhances to 0.109 min(-1) with addition of TEA. In the absence of a reducing agent, acidic to neutral pH favors dechlorination of 4-CP. The final product of dechlorination was estimated to be phenol by performing HPLC, LCMS and NMR analysis. Based on the results, a probable dechlorination mechanism of 4-CP is also proposed. It can be concluded that the catalytic hydrodechlorination is an effective and economical technique for dechlorination of 4-CP and it has a potential for the dechlorination of other toxic derivatives of chlorinated aromatics. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: 4-Chlorophenol; Cl- scavenger; Hydrodechlorination; Raney Ni; Recycling of catalyst; Without reducing agent